189 Outcomes in Appendicitis During The COVID-19 Pandemic: A Single Center Report Of 36 Cases. (12th October 2021) - Angamuthu, N; Mirnezami, R; Knowles, J
Abstract: Introduction: Surgical management of acute appendicitis(AA) during the first peak of COVID-19 was modified somewhat in order to mitigate concurrent infection. Early in the pandemic an open approach was preferable. The management of AA at a single surgical unit over three months during the COVID-19 outbreak is presented. Method: Data on patients diagnosed with AA (3 rd March 2020 to 4 th May 2020) were analysed. Management strategies, morbidity, length of stay and readmissions were evaluated. Results: Median age was 45 years (range 6-75) with a male: female ratio of 2.7:1. The mean white cell count and CRP were 14.7(5.4-25) and 121.6(1- 545), respectively. Appendicectomy (28/36;77.8%) was performed laparoscopically in 23(82.1%) and open in 4(14.3%); 13.9%(5/36) of AA, were managed conservatively. Among the COVID-19 positive patients(5/36), 4 were managed laparoscopically, one needed a laparotomy. Considering COVID-19 positive vs negative/not done status, conversion was seen 50%(2/4) and 5.3%(1/19) respectively. A difference in mean length of stay was noted (positive vs negative/not done = 10.4 days vs 3.43 days). Morbidity was 16.7%(6/36) with a re-admission rate of 11%(4/36). Conclusions: Surgical units need to be flexible to modify their management plans as the COVID-19 pandemic evolves. Awaiting USS/CECT, wait and watch policy related delays should be avoided when possible. A higher conversion rate, morbidity and readmission rate were noted in this cohort of patients, potentially the result of more complicated inflammation, as patients may present late owing to apprehensions regarding their safety while attending hospital.